Melt flow and solidification during infiltration in making steel matrix syntactic foams. Issue 15 (13th October 2019) - Yang, Quanzhan; Yu, Bo; Hu, Huasi; Hu, Guang; Miao, Zhiquan; Wei, Yanpeng; Sun, Weiqiang
ABSTRACT: Steel matrix syntactic foam is a promising lightweight and energy absorbing material. In this study, an infiltration casting technology is developed to prepare syntactic foams, which brings in alumina hollow spheres with an average size of around 3.97 mm to make the pores and enhance the properties of the foams. During the process, melt flow along with heat transfer during the infiltration is investigated. The study shows that melt flow and velocity distribution of molten steel are significantly unstable; the critical solid fraction of the steel is 0.67; and the alumina ceramic mould in which the foams are prepared must be preheated to at least 1000°C to prevent incomplete infiltration. Finally, the microstructure of syntactic foams is studied.